Strigeid parasites of Circus buffoni from Argentina, with the description of a new species of Parastrigea Szidat, 1928 - Drago, Fabiana Beatriz (2018)
Studying the Helminthological Collection of Museo de La Plata (MLP-He), several specimens of digeneans, recovered parasitizing a long-winged harrier, Circus buffoni (Accipitridae) from Buenos Aires Argentina, were analysed. The morphological and morphometric analysis of these specimens revealed the presence of two strigeid species, one of them new for science. Parastrigea buffoni n. sp. is characterised by a forebody differentiated in a retractile cephalic region with a large opening and a balloon-shaped collar region or collerette, suckers located in cephalic region, holdfast organ with well development dorsal and ventral lips that can emerge through opening, a claviform hindbody, a large copulatory bursa with muscular ring (Ringnapf) and a genital cone well delimited, crossed by a sinuous hermaphroditic duct with internal rugae. The euryxenous parasite, Strigea falconis brasiliana, is briefly described, parasitizing a new host. This is the first record of helminths parasitizing long-winged harrier.